Robust H∞ control of uncertain impulsive switched systems. Issue 1 (22nd September 2020) - Li, Chunyang; Jiang, Junchao; Lian, Jie
Abstract: This paper considers robust H ∞ control of impulsive switched systems with time‐varying uncertainties and nonlinear impulsive increments. The impulses are not required to synchronize the switching. Instead, the impulse sequences follow an average impulsive interval assumption, in which the restriction on common lower (or upper) bound of two consecutive impulses is dropped. By using the multiple Lyapunov function and average dwell time method, even with high impulse frequency, the robust H ∞ control performance can still be guaranteed under some sufficient conditions. Finally, the efficiency of the proposed results is demonstrated by a numerical example.